Technological interventions to reduce the drudgery of women farmers in post-harvest operations of millets - Chapke, Rajendra R.; Srinivas, A.; Anuradha, N.; Leela, Y. Sree (Indian Farming, 2026)
In view of addressing the problem of drudgery experienced by women farmers in traditional and improved millet post-harvest practices, including the use of power-operated machinery, a detailed analysis was carried out on millet post-harvest operations using relevant ergonomic parameters. The study involved 32 farm women from Chalki and Gangapur villages of Telangana state, who were beneficiaries of the Farmers FIRST Project. The findings revealed that threshing and winnowing were the most physically demanding and time-consuming operations under traditional practices. Adoption of improved technologies significantly reduced working hours, particularly in flatbread (chapatti) making and other millet post-harvest operations. Moreover, the use of improved machinery helped minimise health-related issues, enhanced work efficiency, increased productivity, and contributed to improve income generation and livelihood security of farm women.